Coordination engineering in Nd3+-doped silica glass for improving repetition rate of 920-nm ultrashort-pulse fiber laser - Wang, Yafei; Chen, Yinggang; Wang, Shikai; Wang, Meng; Zhang, Lei; Feng, Suya; Yu, Fei; Dong, Guoping; Wen, Lei; Chen, Danping; Yu, Chunlei; Hu, Lili (Advanced Photonics Nexus, 2023)
Ultrashort pulses at 920 nm are a highly desired light source in two-photon microscopy for the efficient excitation of green fluorescence protein. Although Nd[sup.3 + ]-doped fibers have been utilized for 920-nm ultrashort pulse generation, the competitive amplified spontaneous emission (ASE) at 1.06 μm remains a significant challenge in improving their performance. Here, we demonstrate a coordination engineering strategy to tailor the properties of Nd[sup.3 + ]-doped silica glass and fiber. By elevating the covalency between Nd[sup.3 + ] and bonded anions via sulfur incorporation, the fiber gain performance at 920 nm is enhanced, and 1.06-μm ASE intensity is suppressed simultaneously. As a result, the continuous-wave laser efficiencies and signal-to-noise ratio at 920 nm by this fiber are significantly enhanced. Importantly, the stable picosecond pulses at 920 nm are produced by a passive mode-locking technique with a fundamental repetition rate up to 207 MHz, which, to the best of our knowledge, is the highest reported repetition rate realized by Nd[sup.3 + ]-doped silica fibers. The presented strategy enriches the capacity of Nd[sup.3 + ]-doped silica fiber in generating 920-nm ultrashort pulses for application in biophotonics, and it also provides a promising way to tune the properties of rare-earth ion-doped silica glasses and fibers toward ultrafast lasers.